VD_FINDINFO Pron / 2011 / 140 vom 30. November 2011 - VD Tribunal cantonal (2011)
DÉCISION D'IRRECEVABILITÉ, JURIDICTION GRACIEUSE, CONCLUSIONS | 132 al. 1 CPC (CH), 132 al. 2 CPC (CH), 248 CPC (CH), 321 al. 1 CPC (CH), 56 CPC (CH), 109 al. 3 CDPJ